Transposon Tn917lacZ mutagenesis of Bacillus subtilis: identification of two new loci required for motility and chemotaxis. - Zuberi, A R (1990)
We have used Tn917lacZ to mutagenize the Bacillus subtilis chromosome and have isolated mutants that are defective in chemotaxis and motility. Mapping of the transposon inserts identified two new loci. Mutations in one of these loci generated mutants that had paralyzed flagella. Accordingly, we designate this a mot locus. The other locus is closely linked to the first and encodes proteins specifying chemotaxis functions. This locus is designated the cheX locus. Both the mot and cheX loci map close to ptsI. An additional transposon insert that maps in the hag locus was obtained. The pattern of beta-galactosidase expression from some of the transposons suggested that the mot locus is regulated by sigD, a minor sigma factor of B. subtilis. The cheX locus appeared to be under the control of vegetative sigA. Four transposon inserts were mapped to a previously characterized che locus near spcB. These mutants did not produce flagellin and were defective in the methylation of the methyl-accepting chemotaxis proteins. This locus probably encodes proteins required for flagellum biosynthesis and other proteins that are required for the methylation response.